1999
DOI: 10.1002/(sici)1097-0215(19990719)82:2<237::aid-ijc14>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

FGF7/KGF triggers cell transformation and invasion on immortalised human prostatic epithelial PNT1A cells

Abstract: Fibroblast growth factor 7 (FGF7/KGF) is synthesized exclusively by fibroblasts in normal tissues; it acts as a potent mitogen on epithelial cells, through interaction with the FGF7‐specific receptor FGFR2/IIIb. To examine the importance of this growth factor both to prostate physiology and to prostate‐cancer progression, we have tested the exogenous effect of FGF7. Thus, by mimicking the paracrine pathway (on proliferation, growth in soft agar and invasion) on the human prostatic epithelial cell line PNT1A po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Therefore, we next investigated whether IGFBP2 could alter these effects. We treated late-passage E6/7-HFKs with KGF in the presence or absence of IGFBP2 and showed that IGFBP2 was sufficient to inhibit KGF induction of ETS2 and MMP1, known modulators of the invasive process ( Fig 6E ) [ 40 , 41 ]. This implied a crucial role for the IGF pathway in the regulation of invasion.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we next investigated whether IGFBP2 could alter these effects. We treated late-passage E6/7-HFKs with KGF in the presence or absence of IGFBP2 and showed that IGFBP2 was sufficient to inhibit KGF induction of ETS2 and MMP1, known modulators of the invasive process ( Fig 6E ) [ 40 , 41 ]. This implied a crucial role for the IGF pathway in the regulation of invasion.…”
Section: Resultsmentioning
confidence: 99%
“…The reason for differences in this pattern is not clear but may represent cell and tumour specific differential utilisation of the FRS proteins. Despite the lack of over-expression we did observe that FRS2 and FRS3 suppression had a significant and specific inhibitory effect in cancer cell lines whereas it had no discernible effect on PNT2 benign prostate cells which are known to express FGF receptors and respond to FGF stimulation [32,33]. Wang et al have previously shown that the quantity and quality of FRS2 phosphorylation is dependent on the cellular context and type of activating FGFR [34].…”
Section: Discussionmentioning
confidence: 96%
“…Culture media used are described in supplementary methods. Cells were treated with 10 -9 M FGF7 (Peprotech) [49], 5μM of the FGFR inhibitor, AZD4547 (Selleck Chemicals) or 1μM of the PI3K inhibitor, ZST K474 (kind gift from E. Ciraolo).…”
Section: Methodsmentioning
confidence: 99%